Pengaruh Sistem Informasi SDM dan Pengembangan Karir Terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening di Puskesmas Pauh Kambar - Rezky Aditya; Muhammad Afuan; Chintya Ones Charli (CV. ITTC INDONESIA, 2026)
Human resources are all the abilities or potential of the population within a certain area along with their demographic, social, and economic characteristics that can be utilized for development purposes. The purpose of this study is to find out how much the Human Resource Information System and Career Development affect Employee Performance, with Job Satisfaction as an intervening variable, at Pauh Kembar Community Health Center. The method used is Structural Equation Modeling (SEM) analysis with Partial Least Square (PLS), distributing questionnaires to 94 respondents. The results of the study showed: There is a positive and significant effect of the Human Resource Information System on Job Satisfaction at Pauh Kembar Community Health Center. There is a positive and significant effect of Career Development on Job Satisfaction at Pauh Kembar Community Health Center. There is a positive and significant effect of the Human Resource Information System on Employee Performance at Puskesm